2022
DOI: 10.3390/ijerph19137852
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences for Health Indicators in a Sample of School Dropout Adolescents: A Pilot Study

Abstract: Background: The ever-increasing prevalence of school dropout (SD) highlights the need to gain insight into risk factors for dropout causes and consequences. The aim of this study was to evaluate the gender differences for health indicators in a sample of school dropout adolescents. Methods: Data were collected regarding 450 adolescent’s SD (19 ± 2 years; 308 males), and health-related quality-of-life (HRQoL) and risk behaviors were assessed by means of a standardized questionnaire. Results: The results reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, it is important to emphasize that this is a first pilot study conducted on school-dropout adolescents, who are therefore potentially more exposed to risk factors, as the little literature aimed at this adolescent population group indicates. A recent work of our group revealed that school-dropout girls are characterized by a compromised health indicator profile in terms of both risk behaviors, including EDs [ 38 ]. The study of the dropout phenomenon is new, as most of the evidence focuses on the long-term effects of dropping out of school, but there are no studies to our knowledge on the short- and medium-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important to emphasize that this is a first pilot study conducted on school-dropout adolescents, who are therefore potentially more exposed to risk factors, as the little literature aimed at this adolescent population group indicates. A recent work of our group revealed that school-dropout girls are characterized by a compromised health indicator profile in terms of both risk behaviors, including EDs [ 38 ]. The study of the dropout phenomenon is new, as most of the evidence focuses on the long-term effects of dropping out of school, but there are no studies to our knowledge on the short- and medium-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…If the school experience is a good one, one can talk about the child's positive adaptability in school (Wang & Gordon, 2012), but, if the child loses their motivation to go to school, he disconnects himself from anything related to school -colleagues and friends -the phenomenon of school disengagement comes up which most of the time leads to absenteeism and school dropout (Ames, 1992). In the last decade, nearly 1.7 million of the more than 6 million students enrolled in the first year of high school did not make it to their senior year (Mastorci et al, 2022). Among the causes we can find unwanted events from school, bad interpretations of what the school context means and also the stressful and traumatizing life events (in the family or in society).…”
Section: School Satisfaction -A Predictor Of Students' Life Satisfactionmentioning
confidence: 99%